Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournaments Berbantuan Kahoot terhadap Pemahaman Konsep IPAS pada Murid Sekolah Dasar (Penelitian Kuasi Eksperimen Kelas IV di SDN 239 Cigondewah, Kota Bandung) - Millawati Nurhasanah; Darda Abdullah Sjam; Siti Sholihah Nurfaidah (Mataram University, 2026)
This research was motivated by the low level of elementary school students' understanding of Integrated Science and Social Studies (IPAS) concepts, which was caused by teacher-centered learning that limited students' active participation in the learning process. This study aimed to describe the learning process, identify the differences in students' conceptual understanding of IPAS between the experimental and control classes, and determine the magnitude of the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Kahoot media on fourth-grade elementary school students' conceptual understanding of IPAS. This study employed a quasi-experimental method using a Nonequivalent Control Group Design. The population consisted of all fourth-grade students of SDN 239 Cigondewah, Bandung, in the 2025/2026 academic year. The sample comprised Class IV-B as the experimental class, which was taught using the Teams Games Tournament (TGT) cooperative learning model assisted by Kahoot, and Class IV-A as the control class, which received conventional instruction. Data were collected through pretests, posttests, and observation sheets of teachers' and students' learning activities. The data were analyzed using normality tests, homogeneity tests, the Mann–Whitney U test, and effect size analysis. The results showed that the learning process in the experimental class was implemented very well, with teacher and student activity percentages both reaching 90%. The Mann–Whitney U test produced an Asymp. Sig. (2-tailed) value of < 0.001 (< 0.05), indicating a significant difference in students' conceptual understanding of IPAS between the experimental and control classes. Furthermore, the effect size analysis yielded a Cohen's d value of 2.538, which falls into the very large effect category. Therefore, it can be concluded that the Teams Games Tournament (TGT) cooperative learning model assisted by Kahoot has a very large effect on improving fourth-grade elementary school students' conceptual understanding of IPAS.